Kajian Produksi Aflatoksin B1 Kasar dari Isolat Kapang Aspergillus Flavus Lokal pada Media Jagung dan Jagung+Kacang Tanah - listya purnamasari; Ali Agus; Cuk Tri Noviandi (Faculty of Animal Science, Universitas Gadjah Mada, 2016)
Aflatoxin, which known as toxigenic compound, is a secondary metabolite produced by Aspergillus flavus and A. parasiticus. Aflatoxin is found in both food and feed stuffs, such as: corn and peanut. Aflatoxin standard is needed in every research of aflatoxin contamination. But it is rather difficult to get. It is imported, high costs, and take times. The aim of the research is to assess the potential local isolate of A. flavus to producing aflatoxin that can be used to be the alternative aflatoxin standard. Local mold of A. flavus FNCC 6122 and FNCC 6109 are got from PAU University of Gadjah Mada. Isolate was enriched on PDA medium for 5 days and move to corn medium of corn+peanut combine medium for 10-15 day at 25ºC. The variables was the content of AFB1 by ELISA test. The result is shown that isolat FNCC 6122 produced higher AFB1 than isolate FNCC 6109. The combine of corn and peanut medium stimulated FNCC 6122 to produce higher AFB1 and has potency to be the candidate of standard aflatoxin. In conclusion, the peanut addition on the medium would initiate increasing of the aflatoksin B1 level.